Lactobacillus (L. plantarum & L. rhamnosus) and Saccharomyces (S. cerevisiae): effects on performance, biochemical parameters, ammonium ion in manure, and digestibility of broiler chickens - Kirsten Leal; Linda Truong; Elizabeth Maga; Annie King (Poultry Science, 2023)
ABSTRACT: Two strains of Lactobacillus combined with Baker's yeast (Saccharomyces cerevisiae) used as probiotics were evaluated to replace antibiotics in poultry flocks by reducing ammonia emissions in manure of broilers without comprising performance or health. One-day-old Cobb 500 broilers (600) were fed starter, grower, and finisher diets as control (CON); probiotic S. cerevisiae, inclusion rate at 4.26 × 106 CFU/kg of feed (SCY); probiotic L. plantarum and L. rhamnosus, inclusion rate at 4.35 × 108 CFU/kg of feed (LPR) for each; and a combination of Lactobacillus plantarum and L. rhamnosus at 4.35 × 108 CFU/kg of feed for each plus Saccharomyces cerevisiae and 4.26 × 106 CFU/kg of feed (SWL). The 4 treatments had 5 replicates (pens), each with 30 broilers. Performance was measured weekly as feed consumption, weight gain, BW, and feed conversion ratio (FCR) over a 6-wk grow-out period. Accompanying biochemical analyses included lipase activity of the pancreas, liver weight, and uric acid (UA) concentration in liver. Albumin, total protein, UA, ammonia, and blood urea nitrogen (BUN) were measured in serum. Ammonium (NH4+) in manure and apparent ileal digestibility from digesta were also measured. Significance was determined at P ≤ 0.05. Results showed that biochemical analyses had no significant treatment effect; however, there were significant temporal changes in performance measures for individual treatments. Feed consumption increased over time for all treatments (P = 2.00 × 10−16). CON had lower weight gain in wk 2 (P = 0.013) compared to all treatment and the lowest BW in wk 5 (P = 0.0008) and wk 6 (P = 0.0124) compared to SWL. Specific probiotic strains, with well-defined inclusion rates, and surrounding environmental analyses of present microbes are needed to ascertain effects of probiotics. Other important areas for investigation include 1) confirmation of probiotics present in the digesta/ceca and how they alter the microbiota within the gastrointestinal (GI) tract and 2) the serum heterophil:lymphocyte ratio to further examine potential immune responses to the probiotics.